AN ANALYSIS OF THE ENGLISH SPEAKING AND WRITING SKILL LEVEL OF TOUR GUIDES IN TRENGGALEK’S TOURIST VILLAGES - Dwi Wahyuningtyas; Wahyu Kyestiati Sumarno; Ria Arista Asih; Fathika Endriana; Khofiatul Rosdiana Windiarti; Naajihah Mafruudloh (Journey: Journal of English Language and Pedagogy, 2022)
Despite the pivotal role of local tour guides to promote tourist attractions in their region, most of them cannot use English communicatively. There is a need to upskill their English level through a training program. This study aims to evaluate Trenggalek’s local tour guides after joining a series of training on Speaking and Writing in English. This study employs a qualitative design with the test results analysis. Five tour guides were tested through verbal and written assessment through a contextualized framework that fit Indonesians’ characteristics as EFL learners. Their abilities were analyzed through adapted rubrics and scoring criteria. Results show that only a few tour guides successfully upgraded their English skills. However, they showed more diverse Speaking abilities compared to their Writing ability. These findings imply that more focus should be put on the training of Speaking skill, and that more workshops should be presented in series coupled with follow-up activities to get tour guides used to using English.